2021
DOI: 10.3390/pr9060935
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift in Tissue Engineering: From a Top–Down to a Bottom–Up Strategy

Abstract: Tissue engineering (TE) was initially designed to tackle clinical organ shortage problems. Although some engineered tissues have been successfully used for non-clinical applications, very few (e.g., reconstructed human skin) have been used for clinical purposes. As the current TE approach has not achieved much success regarding more broad and general clinical applications, organ shortage still remains a challenging issue. This very limited clinical application of TE can be attributed to the constraints in manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…10 Several technologies can also be combined to optimize scaffold properties for the regeneration of a specific tissue 53 or imitate in vivo -like tissue development processes. 54…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Several technologies can also be combined to optimize scaffold properties for the regeneration of a specific tissue 53 or imitate in vivo -like tissue development processes. 54…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the work of Entezari et al , 67 who demonstrated numerically the possibility of using weak biomaterials in modular scaffolds for repairing large bone defects, with only few percent of strain being sufficient to promote osteogenesis, supports our proposed use of the present scaffold for the repair of non and load-bearing tissues. The bioabsorbable scaffold developed here can also be used in bottom-up tissue engineering strategies, 54,68 culturing different cell types on different fabric layers, which assembled could better mimic the native tissue environment and improve tissue healing. Even though some scaffold requirements are specific to each tissue and a single scaffold design is unlikely to meet the requirements of all human tissues; we propose bioabsorbable warp-knitted spacer fabrics as versatile platform for scaffold manufacturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusting bottom-up processes (i.e., the directed or self-assembly of a scaffold from smaller elements or modules, feasibly with various modules aimed to perform distinct functions) for tissue engineering is a major challenge, and numerous attempts to print synthetic biodegradable/biocompatible scaffolds have been made since the first use of fused deposition modeling for tissue engineering applications. , Here, 3D bioprinting is a promising recent advancement with the ability to simultaneously deposit single or blended supportive matrices and living cells (collectively called bioink) and the potential to assist in the fabrication of well-organized 3D vascular networks. ,,, Various types of rapid prototyping methods have been established to enable the creation of macroscopic structures of deposited biomaterials, including gel deposition using syringe-based approaches, stereolithography, and solid freeform manufacturing. While both 3D printing and 3D bioprinting use a 3D prototype to fabricate constructs in a layer-by-layer manner, 3D bioprinting encompasses the use of both cell-loaded bioinks and other biological agents to build a living cell-laden scaffold.…”
Section: Three-dimensional Printing Techniques For Biomimetic Structuresmentioning
confidence: 99%
“…Over the years, bottom-up tissue engineering was developed to take the place of top-down tissue engineering [17,18]. This method is usually used to fabricate function units, such as cell aggregations and cell sheets, which constructs bigger tissues or organs by using the modular assembly approach [1,11,16,19,20].…”
Section: Introductionmentioning
confidence: 99%